Highly-conducting molecular circuits based on antiaromaticity - Shintaro Fujii (Nature Portfolio, 2017)
Antiaromatic molecules are predicted to have unusual charge transport properties, but are notoriously unstable and reactive. Here, the authors successfully fabricate an antiaromatic molecular circuit, based on a macrocyclic complex, displaying much higher conductance than its aromatic counterpart.